Variability of Calodium hepaticum eggs from sigmodontine host species through geometric morphometric analysis. (17th October 2022) - Fantozzi, M.C.; Reguera-Gomez, M.; Beldomenico, P.M.; Mas-Coma, S.; Bargues, M.D.; Valero, M.A.
Abstract: Calodium hepaticum is a zoonotic nematode with a worldwide distribution. Although the host range of C. hepaticum includes a wide spectrum of mammals (including humans), this parasite is predominantly associated with the families Muridae and Cricetidae. Several Sigmodontinae species from Argentina were found to be infected by C. hepaticum, with a high prevalence in Akodon azarae . The present study focuses on C. hepaticum eggs from natural infection of three species of sigmodontine rodents from Argentina. Eggs were genetically characterized (intergenic 18S rRNA region). The objectives of this work are: (i) to propose a new analytical methodology; and (ii) to morphologically characterize C. hepaticum eggs, from three Sigmodontinae species ( A. azarae, Calomys callidus and Oligoryzomys flavescens ). Analyses were made by the Computer Image Analysis System based on the new standardized measurements and geometric morphometric tools. The resulting factor maps clearly illustrate global size differences in the parasite eggs from the three Sigmodontinae species analysed. The degree of similarity between egg populations was assessed through pairwise Mahalanobis distances, showing that the largest distances were detected between parasite eggs from C. callidus and O. flavescens . Herein, the phenotypical plasticity of C. hepaticum eggs is shown. Significant positive correlations were obtained between each egg parasite principal component 1 and rodent corporal characteristics: weight; liver weight; rodent length; and rodent body condition. The usefulness of the geometric morphometric analysis in studies of the relationship between C. hepaticum and its host must be highlighted. The high prevalence observed in A. azarae, associated with the wide size range of the parasite eggs evidenced by principal component analysis, suggests A. azarae to be the Sigmodontinae host species that plays the most important role as reservoir host for C. hepaticum in the New World.